The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/15563650701781931
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic intravenous medication errors reported to the PIC Erfurt

Abstract: Approximately 0.1% of all calls registered by the PIC Erfurt from 1997 to 2006 concerned IIME. Thirty-two percent of IIME followed to a known outcome resulted in severe symptoms. These data show that IIME can be harmful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Actually, two studies from Germany (only intravenous wrong route) found a frequency of 0.03% [9] and 0.01% [10], respectively, a Finnish study (erroneous route in general) of 0.04% [20], and an Irish study (erroneous route in general) of 0.5% [21]. Nevertheless, a detailed analysis is important and appropriate since every case may deliver new insights into the circumstances of occurrence, resulting symptoms, treatment options, and outcomes, and therefore enable the identification of at-risk situations, with the subsequent possibility to implement effective prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Actually, two studies from Germany (only intravenous wrong route) found a frequency of 0.03% [9] and 0.01% [10], respectively, a Finnish study (erroneous route in general) of 0.04% [20], and an Irish study (erroneous route in general) of 0.5% [21]. Nevertheless, a detailed analysis is important and appropriate since every case may deliver new insights into the circumstances of occurrence, resulting symptoms, treatment options, and outcomes, and therefore enable the identification of at-risk situations, with the subsequent possibility to implement effective prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that medication errors encompass different types such as wrong medication, wrong dose, wrong time, and wrong route [6][7][8]. Within the latter group, parenteral administration errors are particularly relevant because of the potential risk for serious outcomes [9][10][11]. However, information in the literature about the circumstances and consequences of application of medicines by the wrong route is limited and mostly based on single case reports for most specialties.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations